1995
DOI: 10.1088/0953-4075/28/1/008
|View full text |Cite
|
Sign up to set email alerts
|

High harmonic generation in the multiphoton regime: correlation with polarizability

Abstract: A two-step model is suggested to explain relative high harmonic efficiency in different atoms and molecules in the multiphoton regime. We discuss the correlation of the high harmonic yield and the static polarizability for systems with nearly the same ionization potential. The comparison of the theoretical estimations with experimental data shows a good agreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Liang et al [10] compared the conversion efficiency between Ar and Xe and a few diatomic molecules (H 2 , D 2 , N 2 and O 2 ). They showed that for these molecules the conversion efficiency increases with the static polarizability, and gave a theoretical justification to this effect, using a multiphoton type of model [11]. Fraser et al investigated harmonic generation in xenon, butane (C 4 H 10 ) and butadiene (C 4 H 6 ) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Liang et al [10] compared the conversion efficiency between Ar and Xe and a few diatomic molecules (H 2 , D 2 , N 2 and O 2 ). They showed that for these molecules the conversion efficiency increases with the static polarizability, and gave a theoretical justification to this effect, using a multiphoton type of model [11]. Fraser et al investigated harmonic generation in xenon, butane (C 4 H 10 ) and butadiene (C 4 H 6 ) [12].…”
Section: Introductionmentioning
confidence: 99%
“…At this stage the possible processes will be determined by the instantaneous intensity of the laser and the energy of the electron. These processes are emission of high harmonics (Chin and Glovinski 1995), laser-assisted scattering which results in the above threshold ionization (Paulus et al 1994), laser-assisted absorption of photons that through electron-electron correlation can lead to NS ionization (Kuchiev 1996), and finally DR with the parent ion resulting in production of neutral fragments.…”
mentioning
confidence: 99%
“…The size of the radial box is chosen to be sufficiently large in order to completely contain the ionized wave packet during the laser-atom interaction, thus preventing unphysical reflections at the grid boundary responsible for artificial contributions to the momentum expectation value. In the SFA and CVA approaches, the numerical convergence is determined by the choice of discretization in the k 3 and t integrals [cf., Eq. 11].…”
Section: Resultsmentioning
confidence: 99%
“…At that time the basic cutoff law, i.e., the relation between the highest photon frequencies generated and the laser intensity and driving frequency, was established both classically and based on the stationary phase method applied to the strong field approximation. Since then, HHG in molecules [3][4][5][6], extended systems [7,8], and solids [9] has opened new aspects with regard to both the cutoff laws and the production of attosecond light [10] with tunable polarization. Nevertheless, the basic mechanism of HHG from simple atoms with linear polarized light sources is still debated, in particular, the role of the binding potential [11].…”
Section: Introductionmentioning
confidence: 99%